2020
DOI: 10.1108/ilt-07-2019-0273
|View full text |Cite
|
Sign up to set email alerts
|

Role of graphene oxide on the tribological properties of CF reinforcement high strength glass fabric/phenolic laminate composites in water environment

Abstract: Purpose This paper aims to study the tribological properties of high strength glass fabric/phenolic laminate composites reinforced by carbon fiber (CF) with and without graphene oxide (GO) modified. Design/methodology/approach In this study, the tribological performance tests of the composites were conducted on a block-on-ring tester (MRH-03). The applied load, linear velocity and duration of time are 200 N, 0.5 m/s and 120 min, respectively. The friction coefficient and specific wear rate were shown. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In the aspect of friction and wear, higher requirements are put forward for the lubricant embedded in copper plate 2 . By combining graphene oxide (GO) with polyethylene glycol (PEG), we have prepared a solid lubricating material that can replace graphite 3 . In recent years, with the progress and development of nanotechnology, nanomaterials have become the most attractive research hotspot in physics, chemistry, and materials science 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aspect of friction and wear, higher requirements are put forward for the lubricant embedded in copper plate 2 . By combining graphene oxide (GO) with polyethylene glycol (PEG), we have prepared a solid lubricating material that can replace graphite 3 . In recent years, with the progress and development of nanotechnology, nanomaterials have become the most attractive research hotspot in physics, chemistry, and materials science 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 By combining graphene oxide (GO) with polyethylene glycol (PEG), we have prepared a solid lubricating material that can replace graphite. 3 In recent years, with the progress and development of nanotechnology, nanomaterials have become the most attractive research hotspot in physics, chemistry, and materials science. 4 It has become one of the key research directions in tribology to develop high-performance lubricants with anti-friction, wear-resistance, and selfrepair functions based on nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…investigated the micro asperity contact load ratios and lubrication states of the water-lubricated bearing, proposed a new coupled models with consideration of micro-scale asperity contact effects, and pointed out that the asperity contact load ratios can be used as the judging criterion for the interface lubrication regimes transition for water lubricated stern-tube bearings. Cao et al [38] found that the carbon fiber reinforced glass fabric/phenolic laminate composite with a 0.2 wt% graphene oxide modified on the carbon fiber shows the lowest friction coefficient and specific wear rate when siding against the stainless steel under water lubrication. Lin et al [39] predicted dynamic characteristics of high-speed water-lubricated spiral groove thrust bearing (SGTB) considering cavitating effect.…”
Section: Influence Factors Of Water-based Lubricationmentioning
confidence: 99%